2021
DOI: 10.1007/s00710-020-00730-y
|View full text |Cite
|
Sign up to set email alerts
|

SFCA-II type Ca2.46Fe3+8.57 Fe2+0.52Al5.45O24 – an improved structural model for an iron-ore sinter phase

Abstract: Single crystals of SFCA-II with composition Ca2.46Fe3+8.57Fe2+0.52Al5.45O24 have been obtained from synthesis experiments in the temperature range between 1300 and 1200 °C. Diffraction experiments at ambient conditions yielded the following basic crystallographic data: space group P$$ \overline{1} $$ 1 ¯ , a = 10.3016(4) Å, b = 10.4656(4) Å, c = 17.9553(6) Å, α = 90.062(3), β = 89.977(3)°, γ = 109.510(3)°, V = 1824.66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Kahlenberg et al also speculated on whether there exists an upper limit of the Al 2 O 3 solubility in SFCA-I, and recently demonstrated that the alumina-rich starting composition Ca 8 Al 16 Fe 16 O 56 (32 mass% Al 2 O 3 ) formed the SFCA-II-type phase rather than SFCA-I. 20) Therefore, the upper limit for Al 2 O 3 concentration in the SFCA-I structure is likely to be in the range 23-32 mass%.…”
Section: Resultsmentioning
confidence: 99%
“…Kahlenberg et al also speculated on whether there exists an upper limit of the Al 2 O 3 solubility in SFCA-I, and recently demonstrated that the alumina-rich starting composition Ca 8 Al 16 Fe 16 O 56 (32 mass% Al 2 O 3 ) formed the SFCA-II-type phase rather than SFCA-I. 20) Therefore, the upper limit for Al 2 O 3 concentration in the SFCA-I structure is likely to be in the range 23-32 mass%.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of SFCA-I has a continuous structure with "SSP" as one block 12) . In addition to SFCA and SFCA-I, SFCA-II and SFCA-III also have been recently discovered [13][14] . SFCA-II has the periodic structure of both SFCA and SFCA-I, i.e., "SPSSP" as one block.…”
Section: Introductionmentioning
confidence: 99%